Anesthesia Management for Patients with Unruptured Giant Thrombosed Saccular Aneurysms - I Wayan Wahyu Giana Permana; I Putu Pramana Suarjaya; Tjokorda Gde Agung Senapathi (Green Publisher Indonesia, 2026)
A giant aneurysm in the middle cerebral artery (MCA) is a rare condition but has a high risk of rupture, requiring optimal anesthesia planning. This report presents a case of a 33-year-old man with an unruptured giant thrombosed saccular aneurysm in a symptomatic MCA branch since 2018. The patient had undergone several DSA examinations before being planned for craniotomy, aneurysm trapping, and high-flow EC-IC bypass. This report aims to describe the anesthetic management of giant MCA aneurysms undergoing complex surgical procedures to maintain hemodynamic stability and prevent perioperative complications. Physical and neurological examinations were within normal limits, and hemodynamic and laboratory results were stable. Anesthesia management included invasive monitoring, induction using tiopental, remifentanil TCI, and rocuronium, and maintenance of anesthesia with tiopental titration, remifentanil, and low-dose sevoflurane. The surgery lasted 11 hours and 45 minutes, with stable hemodynamic conditions and no intraoperative complications. Postoperatively, the patient was admitted to the ICU with intravenous analgesics. No signs of re-bleeding, hemodynamic instability, or new neurological deficits were observed. The report confirms that anesthesia management in cases of giant MCA aneurysms requires strict control of blood pressure, intracranial pressure, and sympathetic responses during critical phases of induction and extubation. A comprehensive and collaborative approach is essential to prevent complications and support the success of surgery for complex intracranial aneurysms.